Evaluation of the main regulators of systemic iron homeostasis in pyruvate kinase deficiency - Anna Zaninoni; Roberta Marra; Elisa Fermo; Dario Consonni; Immacolata Andolfo; Anna Paola Marcello; Barbara Eleni Rosato; Cristina Vercellati; Wilma Barcellini; Achille Iolascon; Paola Bianchi; Roberta Russo (Scientific Reports, 2023)
Abstract Iron homeostasis and dyserythropoiesis are poorly investigated in pyruvate kinase deficiency (PKD), the most common glycolytic defect of erythrocytes. Herein, we studied the main regulators of iron balance and erythropoiesis, as soluble transferrin receptor (sTfR), hepcidin, erythroferrone (ERFE), and erythropoietin (EPO), in a cohort of 41 PKD patients, compared with 42 affected by congenital dyserythropoietic anemia type II (CDAII) and 50 with hereditary spherocytosis (HS). PKD patients showed intermediate values of hepcidin and ERFE between CDAII and HS, and clear negative correlations between log-transformed hepcidin and log-EPO (Person’s r correlation coefficient =  − 0.34), log-hepcidin and log-ERFE (r =  − 0.47), and log-hepcidin and sTfR (r =  − 0.44). sTfR was significantly higher in PKD; EPO levels were similar in PKD and CDAII, both higher than in HS. Finally, genotype–phenotype correlation in PKD showed that more severe patients, carrying non-missense/non-missense genotypes, had lower hepcidin and increased ERFE, EPO, and sTFR compared with the others (missense/missense and missense/non-missense), suggesting a higher rate of ineffective erythropoiesis. We herein investigated the main regulators of systemic iron homeostasis in the largest cohort of PKD patients described so far, opening new perspectives on the molecular basis and therapeutic approaches of this disease.